On the value sharing of q-c-shift and q-shift monomials of meromorphic functions and their derivatives - Banerjee, Abhijit; Biswas, Tania (Sarajevo Journal of Mathematics, 2024)
In this paper, we employ the notion of weighted sharing to study the uniqueness problems of q-c-shift and q-shift monomials of transcendental meromorphic functions of zero order sharing 1-points. The results in this paper extend some previous results.